Afrobethylus Ramos & Azevedo, gen. nov., a new remarkable Afrotropical genus of Bethylinae (Hymenoptera: Bethylidae) - Ramos, Magno S.; Azevedo, Celso O. (Zootaxa, 2016)
Afrobethylus Ramos & Azevedo, gen. nov. (type species Afrobethylus zulu Ramos & Azevedo, sp. nov.) with six new species, Afrobethylus antankarana Ramos & Azevedo, sp. nov. (Madagascar), A. antemoro Ramos & Azevedo, sp. nov. (Madagascar), A. bapedi Ramos & Azevedo, sp. nov. (South Africa), A. swazi Ramos & Azevedo, sp. nov. (South Africa), A. vezo Ramos & Azevedo, sp. nov. (Madagascar), A. zulu Ramos & Azevedo sp. nov. (South Africa) are described and illustrated. This genus is characterized by having the antenna with ten flagellomeres; the forewing with second radial cell closed; the female genitalia with dorsal ramus of second valvula broadly enlarged, and the presence of proximal projection starting from the base of second valvifer. A key to the species of Afrobethylus based on females is provided.